Analisis Pembangunan Desa Sungai Selari Kecamatan Bukit Batu Kabupaten Bengkalis dalam Mewujudkan Sustainable Development Goals Desa - Jifa Hang Malay; Dadang Mashur (Jurnal Ilmiah Wahana Pendidikan, 2023)
Village Sustainable Development Goals is a development concept that prioritizes environmentally friendly development and respects the culture and needs of local communities. Permendesa PDTT No. 13 of 2020 concerning Priorities for the Use of Village Funds in 2021 is an effort to create equality and equitable development in Indonesia. This study uses the theory of Fonseca and Carvalho (2019: 5) which states that to fulfill sustainability it is necessary to achieve the 3 dimensions of SDGs that balance development in the economic, social and environmental dimensions. This study aims to determine the development of Sungai Selari Village, Bukit-Batu District, Bengkalis Regency in realizing the Village SDGs. This study uses qualitative research methods with a descriptive approach. The result of this study is that Sungai Selari village only implemented 11 of the 18 goals of the Village SDGs. Sungai Selari Village only implemented 2 of the 5 economic dimensions of the Village SDGs, 2 of the 5 social dimensions of the Village SDGs, and 1 of the 8 environmental dimensions of the Village SDGs. The development carried out in Sungai Selari Village based on the dimensions of sustainable development has not been able to realize the Sustainable Development Goals of the Village. The non-realization of the Village SDGs in Sungai Selari Village has several inhibiting factors, including the lack of village development programs and the illegibility or non-findability of data inputted into the SID in the Ministry of Villages' Village Information System.